2022
DOI: 10.6000/1927-520x.2022.11.11
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Role of PIWI Proteins and piRNAs in Reproduction of Water Buffalo (Bubalus bubalis, Linn.)

Abstract: High-fertile and productive dairy animals are important to satisfy the growing population's demand. Sire fertility is one of the essential factors that regulate the overall pregnancy rate of dairy herds. However, sire fertility varies from 10 to 90%, suggesting that male fertility largely accounts for varying fertility levels across the herd. Sub-fertile bulls and females should be identified and discarded promptly to improve the dairy herd's productivity. The most dominant factors implicated in culling are po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 77 publications
0
7
0
Order By: Relevance
“…Real-time ultrasonography has been utilized to identify [35,36,37]. According to Fricke (38), follicles are characterized as fluid-filled structures that possess the ability to absorb ultrasonic waves, resulting in their appearance as black on the screen. This black appearance is referred to as anechoic or non-echogenic.…”
Section: 2mentioning
confidence: 99%
See 1 more Smart Citation
“…Real-time ultrasonography has been utilized to identify [35,36,37]. According to Fricke (38), follicles are characterized as fluid-filled structures that possess the ability to absorb ultrasonic waves, resulting in their appearance as black on the screen. This black appearance is referred to as anechoic or non-echogenic.…”
Section: 2mentioning
confidence: 99%
“…It has been reported that the prediction of stage of cycle in postpartum cows is most accurate when based on palpation findings, good estrus detection like vaginal cytology [38] and progesterone profiles [26,28]. However, in the absence of additional information, a clinician must be aware of the limitations of a diagnosis based on palpation alone.…”
Section: 3mentioning
confidence: 99%
“…Determination of the phases of the estrous is useful in synchronizing the reproductive function of the animals. Vaginal cytology is a simple clinical tool used to detect estrus and the stages of the estrous cycle [2]. This is used in canines to determine the perfect time of breeding [3] and estrus cyclicity in the female [4].…”
mentioning
confidence: 99%
“…Application of vaginal cytology in other livestock is limited vis the need to collect the vaginal cell samples in the field and bring it to the lab for analysis making it time-consuming to the field practitioners. However, studies showed that vaginal cytology is an efficient way to check the estrous stage in water buffaloes that includes the Philippine Carabao, Bulgarian, Brazilian, and Indian buffaloes [2,5,6], cattle [7], and goat [8,9]. This paper discusses the vaginal cytology in water buffalo and its application potential in improving reproductive efficiency in artificial insemination programs.…”
mentioning
confidence: 99%
See 1 more Smart Citation